(untitled) (Sociologisk Forskning, 2022)
New public management (NPM) is a prevalent feature of current sociological study of work life and society, but attempts to give the concept theoretical consistency are scarce. In this article, NPM is placed in a longer historical perspective that includes the rationalization and “disenchantment” of modern society. The impact of NPM on work life and society is discussed with the help of classical sociological theory that characterizes society as composed of value spheres with internal lawful autonomy (Eigengesetzlichkeit). This idea originated with Max Weber and was developed within sociological functionalism, and by Jürgen Habermas. In this article it is used together with latter-day critique against the management of professional activities that partly conflicts with the particularity of professions, which can also be understood as Eigengesetzlichkeit. By applying this framework, the article discusses the conflict that arises when NPM meets society’s value spheres, especially professions. The ambition is to explore the potential of using classical sociological theory to analyze a contemporaneous and controversial subject.